Perfil vertical da temperatura oceânica em anos de eventos do enos - Finotti, Elisângela (2015)
In the present work we studied the vertical profile of the Global Ocean temperature in years of occurrence El Nino-Southern Oscillation events, to better understand the functioning of this phenomenon. For its realization were used three sets of ocean reanalysis: ORAS4 produced by European Centre for Medium-range Weather Forecasts, the GODAS produced by National Centers for Environmental Prediction and SODA produced by Carton and Giese, 2008. The three sets of reanalysis showed the same potential temperature pattern in all layers of depth. The Ocean Temperature Index Equatorial Pacific is very well El Nino-Southern Oscillation events, as detected all El Niños and La Niñas occurred in the period of 52 years. Finally, it is concluded that the proposed new index can be used to determine (characterization) of El Nino-Southern Oscillation events with the same precision as the Oceanic Niño Index, and with superior accuracy for predicting El Nino-Southern Oscillation events as it detects these events several months in advance of the Oceanic Niño Index. Therefore, we can add one more tool to help us predict and better understand the El Nino-Southern Oscillation events.